INTEGRATION CROP LIVESTOCK FOREST (ILPF): a technological strategy for agribusiness - Freire, Daniel do Nascimento; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2022)
The integration Crop-Livestock-Forest applied in the property, the most promising technological practice, totally advantageous for the producer, environment, animals and all those involved in the production chain. The ILPF has some obstacles to its implementation, such as: resistance from small producers, ignorance of the system, traditionalism, reprimand for adopting new technologies, payback time on invested capital (long term) mainly in the forestry component. On the other hand, this modality has numerous advantages such as: intensification and optimization of soil cycling, maintenance and improvements in biodiversity, increase in animal welfare, possibility of application in any size of rural property, improvement of the public image of producers through the society. However, this practice of integration of agricultural, livestock and forestry activities, in order to achieve success in the insertion, it is necessary to elaborate a technical project. This article aims to present the history of this crop-livestock-forest integration system, its modalities, the impacts on society and the economy and the guideline for the formulation of the technical project to incorporate the technological strategy into the ILPF.